2016
DOI: 10.1016/j.jgo.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparing comorbidity scales: Attending physician score versus the Cumulative Illness Rating Scale for Geriatrics

Abstract: The CIRS-G scores and LI-scores had poor agreement, indicating that assessment method affects the registration of comorbidity. Thorough descriptions of comorbidity registrations in trials are paramount due to lack of a standardized assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 230 publications
(369 reference statements)
0
22
0
Order By: Relevance
“…It has been validated as a predictor of long-term mortality when assessed in inpatient [3,5] and residential [4] settings. In a more recent study, however, it was found that non-medically trained raters and oncologists would have varying interpretations of comorbidity when assessing the same patient's medical records [6]. The Charlson Comorbidity Index (CCI) has been extensively studied and validated as a predictor of re-hospitalization [7], functional decline [8,9], and mortality in a number of populations [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been validated as a predictor of long-term mortality when assessed in inpatient [3,5] and residential [4] settings. In a more recent study, however, it was found that non-medically trained raters and oncologists would have varying interpretations of comorbidity when assessing the same patient's medical records [6]. The Charlson Comorbidity Index (CCI) has been extensively studied and validated as a predictor of re-hospitalization [7], functional decline [8,9], and mortality in a number of populations [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, mean CIRS-SI was 1.03 (SD=0.31) and median CIRS-CI was 2 (range 1-5) equivalent to a moderate comorbidity. The mean number of diagnoses at discharge was 5.9 (SD=2.3), the median number of clinical tests performed during hospitalization was 8 (range [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], and the mean number of medications prescribed at discharge was 8 (SD=3.2).…”
Section: Resultsmentioning
confidence: 99%
“…12 To the best of our knowledge, an objective measure of patient's clinical complexity, considering all the characteristics and variables of a specific health care setting, is lacking. 17,18 The major weakness of the used methods is that the staff workload is conceptualized at a macro level, without taking into account the specific organizational characteristics (e.g., physical layout, information technology available) that may significantly affect workload. 19 When performing their tasks, clinicians and nurses encounter different situations and patients, which are determinants of the situation-and patientlevel workloads.…”
Section: Discussionmentioning
confidence: 99%
“…There is often poor or weak correlation among scales. 5,11,12 It is likely that specific components of comorbid disease have an association with outcomes in advanced lung cancer rather than a composite score that may overstate the "weight" of some conditions and undervalue others. A recent report found that specific components of comorbidity, i.e., congestive heart failure and cerebrovascular disease demonstrated a negative association with overall survival but not the composite score as a single variable.…”
Section: How Is Comorbidity Assessed?mentioning
confidence: 99%
“…4 In the current issue of the Journal of Geriatric Oncology, Kirkhus et al report on two methods of measuring comorbidity in patients treated on a Norwegian multicenter phase III trial comparing two first-line chemotherapy regimens in advanced NSCLC. 5 This is a well-conducted secondary analysis comparing a validated tool (CIRS-G, Cumulative Illness Rating ScaleGeriatric) to a simpler tool devised by local investigators (LI) to assess comorbidity and its impact. Investigators found that more comorbidities and a higher severity were registered by the CIRS-G compared to the LI score.…”
mentioning
confidence: 99%